The 5-HT1A receptor and 5-HT transporter in temporal lobe epilepsy - Martinez, Ashley; Finegersh, Andrey; Cannon, Dara M; Dustin, Irene; Nugent, Alison; Herscovitch, Peter; Theodore, William H (Neurology, 2013)
To study 5-HT transport and 5-HT1A receptors in temporal lobe epilepsy (TLE) and depression. Thirteen patients had PET with [(11)C]DASB for 5-HTT and [(18)F]FCWAY for 5-HT1A receptor binding, MRI, and psychiatric assessment. Sixteen healthy volunteers had [(11)C]DASB, 19 had [(18)F]FCWAY, and 6 had both PET studies. We used a reference tissue model to estimate [(11)C]DASB binding. [(18)F]FCWAY volume of distribution was corrected for plasma-free fraction. Images were normalized to common space. The main outcome was the regional asymmetry index. Positive asymmetry indicates relative reduced binding (reflecting transporter activity) ipsilateral to epileptic foci. Mean regional [(11)C]DASB binding and asymmetry did not differ between patients and controls. [(18)F]FCWAY asymmetry was significantly greater for patients than controls in hippocampus, amygdala, and fusiform gyrus. On analysis of variance with region as a repeated measure, depression diagnosis had a significant effect on [(11)C]DASB asymmetry, with significantly higher [(11)C]DASB asymmetry in insular cortex (trend for fusiform gyrus). In insular cortex, patients had a significant correlation between [(18)F]FCWAY asymmetry and [(11)C]DASB asymmetry. Our study showed increased [(11)C]DASB asymmetry in insula and fusiform gyrus, and relatively reduced transporter activity, in subjects with both TLE and depression, as compared to subjects with TLE alone, implying reduced reuptake and thus increased synaptic 5-HT availability. This finding may represent a compensatory mechanism for 5-HT1A receptor loss. Altered serotonergic mechanisms have an important role in TLE and concomitant depression.